The Program of the Francis A. Countway Library of Medicine - Esterquest, Ralph T. (1967)
The planning of the Countway Library took place in an atmosphere of community interest and support. Architectural planning was effective and harmonious. The building functions well. The program of the Library is briefly described. Serials records, involving 17,000 titles, have been mechanized. A rare books program has been initiated. Since building occupancy, the Library has substituted copy service for the lending of periodicals. For an experimental period, the copy service was cost free. The Aesculapian Room, for non-medical recreational reading, has had the generous support of the Aesculapian Club. Plans for regional library service in New England are based upon an historic commitment of the Boston Medical Library. A MEDLARS regional search center and a national Vision Information Center have been established in the Countway.